L’écologie territoriale et les enjeux de la dématérialisation des sociétés : l’apport de l’analyse des flux de matières - Sabine Barles (Développement Durable et Territoires)
Territorial ecology is quite a new field of research, especially in France. It first of all aims at analysing, and even transforming territorial metabolism, on the basis of both the natural and social process that impact this metabolism. Thanks to several case studies at the regional and département scale, the paper illustrates the contribution of bulk material balances to the understanding of territorial metabolism; studies the main material flows and identifies the three main types of materials involved: construction minerals (the consumption of witch is linked to urban sprawl process), agricultural and food products, fossil fuels. The paper also makes some suggestions in terms of pathways to dematerialisation, and proposes further research developments.